Nonorthodox Economic Approaches to Labor Unions and Union Leadership (Encyclopedia of Diversity, Equity, Inclusion and Spirituality, 2024)
Ideas concerning the role, function, and nature of labor unions and their leadership can be found in 19th century economics literature. Even since this early period, a division between orthodox and non-orthodox approaches toward the study of labor unions can be discerned.  The orthodox framework was formed in the late 19th century with the gradual establishment of Marginalism, and it consolidated itself with the dominance of early neoclassical economics. Orthodox economic theory did not devote much attention to the economic analysis of unions. On the contrary and during the same period, non-orthodox economists such as Sidney and Beatrice Webb and early institutionalists (e.g. Richard Ely), had paid considerable attention to the study of unions, perceiving them as politico-economic organizations and emphasizing their wider role as social institutions (McNulty, 1980). The legacy of those two approaches continued in the 20th century and contemporary analyses of labor unions. The orthodox approach (originating mainly from the work of John Dunlop), generally conceives unions as purely economic units, analogous to firms, which can be studied by applying the standard tools of microeconomic theory. In this framework, the notion of union leadership plays a minimum role. In contrast, the non-orthodox viewpoint (originating mainly from Arthur Ross’ works), embraces a holistic, institutional-political-based attitude to labor unionism (Kaufman, 2002).